Developing Multimodal Mindful Material for Secondary School in Indonesia Post Covid-19 Pandemic - Qonita Aulia Rahma (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This article determines the students' perception towards the usage of multimodal in learning activities, especially English language in the class. The long pandemic has changed the students' learning style, making them back pushed into the usual classroom activity when they are offline but with some upgrading innovation. With the multimodal mindful material approach through student workbook (LKS).  Media that are familiar with offline class students will adapt to the usual learning atmosphere but can still ensure that students have a broad learning experience and a free learning style. Therefore, it is possible for the teacher to accept their different learning abilities. The subjects of this research are 25 ninth grade students of SMPN 15 Malang using research and development methods. Data analysis taken with questionnaire, observation, and documentation with reference model ADDIE (Analysis, Design, Development, Implementation and Evaluation.)